Rzeczywistość rozszerzona w edukacji przełomu dekad: 2019-2021 - Topol, Paweł (Studia Edukacyjne, 2021)
The aim of the article is an attempt to analyze the use of Augmented Reality in educational applications over the last few years. The first part is devoted to defining the concept more precisely, because AR may seem ambiguous. The second part of the article introduces selected educational applications of AR in different subjects or teaching/learning, e.g. in science/mathematics, natural science or in language learning. Research projects for applications in various teaching solutions will also be referenced. The third and final part contains a brief review of AR literature in recent years.